Hybrid Advisory Weight based dynamic scheduling framework to ensure effective communication using acknowledgement during Encounter strategy in Ad-hoc network - Manikandan, A.; Madhu, G. C.; Flora, G. Dency; Parvez, M. Muzammil; Begum, M. Baritha (International journal of information technology (Singapore. Online), 2023)
When several devices or nodes desire to join wirelessly and pass network data among themselves without a central administrator, an ad hoc wireless network is created. Ad hoc networks are networks that are constructed on the fly. In wireless sensor networks (WSNs), the issue of scheduling routing and maximising lifespan has received extensive research. The aforementioned discussion covered a number of strategies that can help WSNs schedule and maximise node lives. Higher performance in maximising the sensor nodes’ lifespan, however, is challenging to achieve. To boost productivity, we combine two fundamental strategies. The first is called the Hybridized Additive Weight Based Dynamic Scheduling Algorithm (HAWDS), while the second is called the Acknowledgement during Encounter strategy (AES) algorithm. The results of this suggested study will enable mobile nodes to be clustered in an ideal way that takes into account a variety of factors, including distance, energy, bandwidth, and stability. Pick the best cluster head first so that the best clustering can be accomplished. Last but not least, pick a limited number of nodes and maintain them in work mode. The data transmission is carried out via the paths that the chosen path is capable of using. In accordance with the outcome of the route selection, identify the list of nodes that are present along the path. The current transmission is set to put the rest of the network’s nodes into sleep mode, and any such nodes that are present along the chosen path are set to awaken. Throughput performance and longevity are enhanced overall by this.